2015
DOI: 10.1007/s10654-015-0029-2
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and risk of dementia up to 27 years later in a large, population-based sample: the HUNT study, Norway

Abstract: The relationship between alcohol consumption and dementia risk is unclear. This investigation estimates the association between alcohol consumption reported in a population-based study in the mid-1980s and the risk for dementia up to 27 years later. The entire adult population in one Norwegian county was invited to the Nord-Trøndelag Health Study during 1984–1986 (HUNT1): 88 % participated. The sample used in this study includes HUNT1 participants born between 1905 and 1946 who completed the questionnaire asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 23 publications
5
67
1
3
Order By: Relevance
“…Our results are in contrast to those of a population study in Norway that found that frequent drinking was associated with increased dementia risk compared to non-frequent drinking [11]. However, in that study, frequent drinkers were defined as those consuming five or more drinks in a 14-day period and comprised only 6.5% of the population, a drinking pattern very different than that observed in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in contrast to those of a population study in Norway that found that frequent drinking was associated with increased dementia risk compared to non-frequent drinking [11]. However, in that study, frequent drinkers were defined as those consuming five or more drinks in a 14-day period and comprised only 6.5% of the population, a drinking pattern very different than that observed in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have reported on the relationship between alcohol consumption and Alzheimer's disease, and have indicated that low levels of alcohol consumption could protect against dementia and reduce the mortality rate of mild Alzheimer's disease (Berntsen et al, 2015;Ilomaki et al, 2015). However, one large-scale study has reported that frequent alcohol consumption is associated with elevated risk of dementia (Langballe et al, 2015). Ethanol is not toxic to the human body; however, the acetaldehyde oxidized from ethanol is toxic.…”
Section: Adh1b Rs1229984 Andmentioning
confidence: 99%
“…Excessive ingestion of alcohol, whether acute or chronic, is responsible for a tremendous disease and disorder, not only alcoholic hepatitis, cirrhosis and hepatocarcinoma, but also a series of other dysfunctions including pancreatitis, cardiomyopathy, hypertension, stroke, and fetal alcohol syndrome [10][11][12][13]. Excessive consumption of alcohol also results in damage to the central nervous system, such as polyneuritis, cerebellar degeneration, alcoholic dementia, pellagra encephalopathy, Marchiafava-Bignami and Wernicke-Korsakoff syndromes [14][15][16]. Moreover, epidemiological studies have identified chronic alcohol consumption as a significant risk a key mediator of hangover syndrome, and demonstrated that various antioxidants could suppress the adverse events caused by alcohol exposure [39].…”
Section: Introductionmentioning
confidence: 99%